2019
DOI: 10.5194/bg-16-785-2019
|View full text |Cite
|
Sign up to set email alerts
|

Automatic high-frequency measurements of full soil greenhouse gas fluxes in a tropical forest

Abstract: Abstract. Measuring in situ soil fluxes of carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O) continuously at high frequency requires appropriate technology. We tested the combination of a commercial automated soil CO2 flux chamber system (LI-8100A) with a CH4 and N2O analyzer (Picarro G2308) in a tropical rainforest for 4 months. A chamber closure time of 2 min was sufficient for a reliable estimation of CO2 and CH4 fluxes (100 % and 98.5 % of fluxes were above minimum detectable flux – MDF, respect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 33 publications
2
29
1
Order By: Relevance
“…Above or below this optimum, soil CO 2 efflux decreased by a maximum factor of 1.4. This finding is in agreement with previous studies performed in the same site (Rowland et al, 2014;Courtois et al, 2019). On the one hand, excess SWC can create a physical barrier for gas diffusion between the soil and the atmosphere, and a biological inhibitor for root and microbial activities because of the decrease, or even absence, of O 2 (Wood et al, 2013).…”
Section: Combined Effects Of Fertilization and Drought On Soil Co 2 Esupporting
confidence: 93%
See 2 more Smart Citations
“…Above or below this optimum, soil CO 2 efflux decreased by a maximum factor of 1.4. This finding is in agreement with previous studies performed in the same site (Rowland et al, 2014;Courtois et al, 2019). On the one hand, excess SWC can create a physical barrier for gas diffusion between the soil and the atmosphere, and a biological inhibitor for root and microbial activities because of the decrease, or even absence, of O 2 (Wood et al, 2013).…”
Section: Combined Effects Of Fertilization and Drought On Soil Co 2 Esupporting
confidence: 93%
“…Furthermore, soil water saturation can create a physical barrier for gas diffusion, and potentially stop the root and microbial activities because of a lack of available O 2 . Studies on drought effects on soil CH 4 flux however remain sparse, although all showed an increase in CH 4 consumption (Davidson et al, 2004(Davidson et al, , 2008 with extremely high spatial heterogeneity (Wood and Silver, 2012;Courtois et al, 2019). In our study however, soils are mainly a source under drought treatment, with highest CH 4 emissions when SWC was about 20% in the dry plots.…”
Section: No Combined Effects Of Fertilization and Drought On Soil Ch contrasting
confidence: 49%
See 1 more Smart Citation
“…Data used in this study can be freely accessed through the Zenodo repository: https://doi.org/10.5281/zenodo. 2555299 (Courtois and Stahl, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, this limitation has been largely overcome by the introduction of computer-controlled automatic sampling systems [11,12]. However, the automatic equipment is usually expensive to install, although increasingly more studies have started to use this new efficient system [13][14][15][16][17]. Thus, for the archived data now available, the observation frequency is often less than once a month, determined according to the practicability of accessing the site, and usually in the daytime.…”
Section: Introductionmentioning
confidence: 99%